2012
DOI: 10.1002/ps.3388
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of the effects of Manilkara subsericea (Mart.) Dubard extracts and triterpenes on the development of Dysdercus peruvianus and Oncopeltus fasciatus

Abstract: The results indicate that extracts and triterpenes from Manilkara subsericea act as potent growth inhibitors of phytophagous hemipteran nymphs. It is also concluded that the mixture of several different molecules in the extracts used produces synergic effects that do not occur after using the triterpenes (PFT) alone. These secondary metabolites in the M. subsericea extracts can potentially be used in integrated control programmes against crop pests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Perhaps, differences in the speed of absorption between HFNE and blank nanoemulsion by insect metabolic systems may explain this not expectable result. Physiological mechanisms of metabolization of these compounds by invertebrates remains unknown [9] and is now under investigation by our research group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps, differences in the speed of absorption between HFNE and blank nanoemulsion by insect metabolic systems may explain this not expectable result. Physiological mechanisms of metabolization of these compounds by invertebrates remains unknown [9] and is now under investigation by our research group.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylthiocholine iodide (ATCI), 5,5-dithiobis-2-nitrobenzoic acid (DTNB), physostigmine (eserine) and acetylcholinesterase from electric eel (type VI-S, C3389-2UK, lyophilized powder) were purchased from Sigma (Sigma-Aldrich Corporation, St Louis, MO). Hexane-soluble fraction from fruits of M. subsericea was previously obtained [9] and stored at 4°C for further utilization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no report of any morphological alterations of R. nasutus in the literature. However, some authors have Bioactivity of the latex from P. amapa on the development of R. nasutus under laboratory conditions reported that natural extracts can cause morphological alterations in insect species (Fernandes et al 2012;Cabral et al 2000). These morphological alterations found using the scanning electron microscopy can hinder the locomotion of the insect and decrease the dispersion activity of the triatomine.…”
Section: Rhodnius Nasutusmentioning
confidence: 99%